Profesor Turun Padang programme Interactive storytelling animations competition - Siti Normaziah, Ihsan (Faculty of Computing, 2024)
The Faculty of Computing at Universiti Malaysia Pahang Al-Sultan Abdullah has organised the Best of the Best Award competition for creating interactive storytelling animations. This programme is part of the "Profesor Turun Padang" Program (PTP).